PDF Mechanical Properties of AISI 316L Stainless Steel Produced Via Selective Laser Melting - Hadi, Raid; Taha, Ziad Aeyad (Iraqi Journal of Laser, 2022)
Abstract Additive manufacturing has been recently emerged as an adaptable production process that can fundamentally affect traditional manufacturing in the future. Due to its manufacturing strategy, selective laser melting (SLM) is suitable for complicated configurations. Investigating the potential effects of scanning speed and laser power on the porosity, corrosion resistance and hardness of AISI 316L stainless steel produced by SLM is the goal of this work. When compared to rolled stainless steel, the improvement is noticeable. To examine the microstructure of the samples, the optical microscopy (OM), scanning electron microscopy (SEM), and EDX have been utilized. Hardness and tensile strength were used to determine mechanical properties. The results indicated that the samples were completely dissolved, and the hardness was 285HV. Compared with the models produced by other parameters, the best 0.3% porosity was obtained using 100 W laser power, a hatching distance of 70 µm, a layer thickness of 30µm, and a scanning speed of 600 mm/sec. In addition, the volumetric energy density value for the best result was 79 J/mm3.